Impact of performance in a mandatory postgraduate surgical examination on selection into specialty training. Issue 3 (29th August 2017) - Scrimgeour, D S G; Cleland, J; Lee, A J; Griffiths, G; McKinley, A J; Marx, C; Brennan, P A
Abstract: Background: The Intercollegiate Membership of the Royal College of Surgeons (MRCS) examination is undertaken by large numbers of trainees in the UK and internationally as a mandatory step within surgical training. Unlike some high-stakes medical examinations, the MRCS is yet to be validated. A quantitative study was undertaken to assess its predictive validity by investigating the relationship between MRCS (Parts A and B) and national selection interview scores for general and vascular surgery in the UK. Methods: Pearson correlation coefficients were used to examine the linear relationship between each assessment, and linear regression analyses were employed to identify potential independent predictors of the national selection score. All UK medical graduates who attempted the interview in 2011–2015 were included. Results: Some 84·4 per cent of the candidates (1231 of 1458) were matched with MRCS data. There was a significant positive correlation between the first attempt score at Part B of the MRCS examination and the national selection score ( r = 0·38, P < 0·001). In multivariable analysis, 17 per cent of variance in the national selection first attempt score was explained by the Part B MRCS score and number of attempts (change in R 2 value of 0·10 and 0·07 respectively; P < 0·001). Candidates who required more than two attempts at Part B were predicted to score 8·1 per cent less than equally matched candidates who passed at their first attempt. Conclusion: This study supports validity of the MRCS examination, and indicates its predictive value regarding entry into specialist training. Graphical Abstract: Performance in the Intercollegiate Membership of the Royal College of Surgeons (MRCS) examination predicts general and vascular surgery national selection first attempt score. This study, the first of its kind for the MRCS, supports both MRCS validity and its predictive validity. Examination performance influences selection into training